The descriptive study of imposter syndrome in medical students - Maqsood, Hamza; Shakeel, Hassan Abdullah; Hussain, Humza; Khan, Ali Raza; Ali, Basit; Ishaq, Asher; Shah, Syed Asfand Yar (International Journal of Research in Medical Sciences, 2018)
Background: Imposter syndrome is characterized by chronic feelings of self-doubt and fear of being discovered as an intellectual fraud. Despite evidence of abilities, those suffering from imposter syndrome are unable to internalize a sense of accomplishment, competence, or skill. Overall, they believe themselves to be less intelligent and competent than others perceive them to be. IS has several potential implications for medical education. The current study was designed to find out the frequency of imposter syndrome among medical students college so that certain measures must be taken to improve the teaching and learning methodologies as well as the curriculum. Methods: A cross-sectional, psycho-social analysis was conducted from March to July, 2018 at Nishtar Medical College, Multan after taking informed consent from the students. Clance Imposter Phenomenon Sclae (CIPS) was used to assess the prevalence and degree of severity of Imposter syndrome among medical chosen on basis of random sampling. The data collected was entered and analysed on SPSS v.20. Results: Two hundred (200) students were selected for the study and were asked to return the completed 20 items questionnaire. One hundred and eighty-nine (189) students returned the questionnaires, so the response rate was 94.5%. Out of 189 students, 121(64.36%) were males and 68(35.97%) were females. According to Clance imposter phenomenon scoring, of the total 189 students the severity of imposter syndrome is as follows: mild, 5(2.64%), moderate,72(38.09%), severe,103(54.49%) and very severe, 09(4.76%). Moreover, third year students were found to have high prevalence and degree of severity of imposter syndrome. Conclusions: Imposter phenomenon exists in a significant percentage of medical students and appears to peak in the third year of medical school. Both genders are at equal risk of having imposter syndrome. It is associated with various psychological illnesses. Further discussion regarding medical education paradigms in light of high levels of imposter phenomenon is needed.